Answer:
T₆₇ = -413
Step-by-step explanation:
Answer:Two solution
Step-by-step explanation:
Hello,
11x + 7 + -3x - 3 = 11x - 3x + 7 - 3 = (11 - 3)x + 4 = 8x + 4
The linear equation y = -6x + 2; -12x - 2y = -4 has no solution
<h3>Linear equation</h3>
y = -6x + 2
-12x - 2y = -4
- Substitute y = -6x + 2 into (2)
-12x - 2y = -4
-12x - 2(-6x + 2) = -4
-12x + 12x -4 = -4
-12x + 12x = - 4 + 4
0 = 0
y = -6x + 2
y - 2 = -6x
x = (y - 2) / -6
-12x - 2y = -4
-12(y- 2)/ 6 - 2y = -4
(-12y + 24) / 6 - 2y = -4
-2y + 4 - 2y = 4
0 = 0
Learn more about linear equation:
brainly.com/question/4074386
#SPJ1
<h2>3</h2>
S<--->T
T<--->S
Same thing
<h2>4</h2>
Both sides a equivalent therefore both triangle areas are also equivalent